The Influence of Organizational Culture and Locus of Control on Employees Performance at Agriculture Department of South Bengkulu - Deka Amlia; Neri Susanti; Nia Indria Sari (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine the influence of organizational culture and locus of control on employee performance at Agriculture Department of South Bengkulu. The sample in this study was 58 employees with State Civil Apparatus (ASN) at Agriculture Department of South Bengkulu. The data was collected using a questionnaire and the analytical method used was multiple linear regression, determination test and hypothesis testing. The results showed that the positive influence between organizational culture and Locus of Control on employee performance at t Agriculture Department of South Bengkulu because the regression direction had a positive direction, namely Y = 9.810 + 0.356X1 + 0.410X2. This illustrates that with the organizational culture of employees at work, their performance will increase. Locus of control has a significant influence on employee performance at Agriculture Department of South Bengkulu, because the significant value of 0.000 is smaller than 0.05. This means that the greater locus of control for the employees at Agriculture Department of South Bengkulu, the performance will also increase. This illustrates that the self-control of the employees will increase the performance of the employees. Organizational culture and locus of control have a significant influence on the performance of employees at Agriculture Department of South Bengkulu, thus the initial hypothesis proposed is proven (Ha is accepted). That is, there is a significant influence between organizational culture and locus of control on performance together. The coefficient of determination of R square is 0.472. This means that organizational culture and locus of control affect performance by 47.2% while the rest is influenced by other causal factors not examined in this study.